Acute toxicity of waters from the urban drainage channels of Santos (São Paulo, Brazil) - Ambrozevicius, Andréa Pimenta [UNESP]; Abessa, Denis Moledo de Souza [UNESP] (My University, 2008)
The objective of this study was to evaluate the toxicity of water which flows toward the beaches of Santos, SP, Brazil. Water samples were collected from eight urban drainage channels and a small creek, in March, April and August 2005. For each sample, some physical-chemical parameters were analyzed: pH, dissolved oxygen, temperature, salinity, presence of free chlorine and total ammonia contents. Acute toxicity tests (48h) with Daphnia similis were also performed with the samples. The level of ammonia was relatively high in the majority of the samples (≥ 1.5 mg/L), and free chlorine was measurable in most of them. Acute toxicity was observed in four water samples (stations 3, 4, 5 and 7), at least in one occasion. The toxicity was positively correlated with the ammonia concentrations and salinity. Because acute toxicity was detected, actions aiming to control the pollution sources and improve the water quality are recommended.
Keywords: Daphnia similis; Ecotoxicology; Toxicity tests; Water pollution; Water quality; Daphnia